Vascular Toxicity Risk Assessment of MC18 and MC70, Novel Potential Diagnostic Tools for In Vivo PET Studies. Issue 5 (16th January 2017) - Fusi, Fabio; Durante, Miriam; Sticozzi, Claudia; Frosini, Maria; Perrone, Maria G.; Colabufo, Nicola A.; Saponara, Simona
Abstract: The P‐glicoprotein (P‐gp) inhibitor MC18 has been recently proposed as a valuable PET tracer to measure P‐gp expression in vivo . The aim of this study was to evaluate the toxic hazard towards the vasculature of MC18 along with the structurally related and more potent P‐gp inhibitor MC70. Their effects on A7r5 and EA.hy926 cells viability, on the mechanical activity of fresh and cultured rat aorta rings as well as on Cav 1.2 channel current (IC a1.2 ) of A7r5 cells were studied. At concentrations >10 μM, MC18 and MC70 decreased cell viability causing evident morphological changes. In fresh rat aorta rings, both compounds (0.1–100 μM) antagonized phenylephrine‐induced contraction in a concentration‐dependent manner, with IC50 values in the range of 1.67–14.49 μM, whereas only MC18 caused a concentration‐dependent decrease of the 60 mM K + (K60)‐induced responses. In rings cultured for 7 days with both compounds (1–10 μM), 10 μM MC70 significantly reduced, while 10 μM MC18 completely prevented the contractile response to both phenylephrine and K60. MC18 and MC70 (0.1–100 μM) inhibited IC a1.2 in a concentration‐dependent manner with IC50 values of 16.81 and 32.13 μM, respectively. These findings demonstrate that MC18‐induced vascular effects took place at concentrations that are at least three orders of magnitude higher than those (≤10 nM) allowing in vivo measurement of P‐gp expression. Thus, MC18, and possibly MC70, can be considered promising PET tools for in vivo P‐gp quantification.